O Assentamento 1º de Maio no contexto da expansão da fronteira agrícola - Miranda Filho, Francisco (2017)
The main purpose of this study is to analyze the family production that has been developed on the 1º de Maio settlement that is located in the city of Colniza of Mato Grosso state. It also tries to understand how they maintain themselves in face of difficulties of accessing the market due to the resistance to the family production through the agribusiness’s advancement towards the northwest of Mato Grosso, agriculture frontier area. In order to analyze and comprehend the process of colonization, its elements and the efficiency of the family agriculture developed by the settlement 1º de Maio and its relation to public policy developed to the settled, the basis comes from a theoretical and methodological aspects from authors as: Ianni (2000), Becker (1990), Martins (1992;1995;2000;2009), Moreno (2005;2007), Oliveira (2007), Stédile (1977;2006;2007) e Santos (1992;2006;2007). The study and the analysis of the data were made based on the dialectical method and in the quality approach, based on the concepts of territory, agriculture frontier, and rural settlement. The analysis presented that differently from occupations in other regions, the occupation movements in the city of Colniza are not related to the Landless Workers' Movement, and therefore they came up spontaneously, without the necessity of a systematic movement. It was verified that the distances from the Colniza city, in relation to large consumer market, the lack of both, financial support and technical assistance influenced on the productive dynamic of the settled. However, the advance in the agribusiness field shows restrictions due to the existence of pedological features in the city of Colniza, by maintaining the same technical level from nowadays, hindering the incorporation of lands to the culture of grains in a large scale. Given this situation the incorporation of the agribusiness occurs secondarily, mainly towards to the production of animal protein in the regional level. It is noticed that despite having limitations to entering in the local agribusiness, it is expanding itself in the region, what creates a worry related to preserving the social and environmental balance, because that may cause a rural exodus, changes in the spatial and economics dynamics, and also cause environmental issues.